Effects of sprint training with or without ball carry in elite rugby players - Seitz, L. B.; Barr, M.; Haff, G. G. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To compare the effects of sprint training with or without ball carry on the sprint performance of elite rugby league players. Methods: Twenty-four elite rugby league players were divided into a ball-carry group (BC; n = 12) and a no-ball-carry group (NBC; n = 12). The players of the BC group were required to catch and carry the ball under 1 arm during each sprint, whereas the NBC group performed sprints without carrying a ball. The 8-wk training intervention took place during the precompetitive phase of the season and consisted of 2 sessions/wk. Sprint performance was measured before and after the training intervention with 40-m linear sprints performed under 2 conditions: with and without ball carry. Split times of 10, 20, and 40 m were recorded for further analysis. A 3-way (group × time × condition) factorial ANOVA was performed to compare changes in sprint performance with and without the ball, before and after the training intervention for both BC and NBC training groups Results: The BC and NBC groups experienced similar improvements in 10-, 20-, and 40-m sprint times and accelerations, regardless of the condition under which the sprint tests were performed (P = .19). Conclusions: Sprint training while carrying a rugby ball is as effective as sprint training without carrying a rugby ball for improving the sprint performance of elite rugby league players.